Change in the micellar aggregation number or in the size distribution?: a dynamic fluorescence quenching study of aqueous cetyltrimethylammonium chloride - Reekmans, Steven (1993)
Aqueous solutions of cetyltrimethylammonium chloride were studied by means of dynamic fluorescence quenching measurements to get information on the micellar aggregation number and size polydispersity as a function of surfactant concentration. The global analysis of multiple decay curves provided estimates with improved accuracy and precision and indicated a reduced polydispersity upon increasing surfactant concentration. As the quenching rate slows with increasing surfactant concentration it is concluded that there is a micellar growth, but that this growth preferably increases the aggregation number for the smaller aggregates in the initially polydisperse solutions.